Simple Cobalt Nanoparticle-Catalyzed Reductive Amination for Selective Synthesis of a Broad Range of Primary Amines - Bingxiao Zheng; Liqin Yang; Yashuang Hei; Ling Yu; Sisi Wen; Lisi Ba; Long Ao; Zhiju Zhao (Molecules)
In the field of green chemistry, the development of more sustainable and cost-efficient methods for synthesizing primary amines is of paramount importance, with catalyst research being central to this effort. This work presents a facile, aqueous-phase synthesis of highly active cobalt catalysts (Co-Ph@SiO2(x)) via pyrolysis of silica-supported cobalt–phenanthroline complexes. The optimized Co-Ph@SiO2(900) catalyst achieved exceptional performance (>99% conversion, >98% selectivity) in the reductive amination of acetophenone to 1-phenylethanamine using NH3/H2. Systematic studies revealed that its exceptional performance originates from the in situ pyrolysis of the cobalt–phyllosilicate complex. This process promotes the uniform distribution of metal cobalt nanoparticles, simultaneously enhancing porosity and imparting bifunctional (acidic and basic) properties to the catalyst, resulting in outstanding catalytic activity and selectivity. The catalyst demonstrated broad applicability, efficiently converting diverse ketones (aryl-alkyl, dialkyl, bioactive) and aldehydes (halogenated, heterocyclic, biomass-derived) into primary amines with high yields (up to 99%) and chemoselectivity (>40 examples). This sustainable, non-noble metal-based catalyst system offers significant potential for industrial primary amine synthesis and provides a versatile tool for developing highly selective and active heterogeneous catalysts.